(3GdSge GdeUjH aj cHO GdNWjHs - (3YjSi (B((3Gdedc GdeYXe(B) (3Hf eMeO (B((3Gdedc GdYGOd(B) (3CHj HcQ Hf CjhH, TQa GdOjf GdCjhHj(B: (3SdWGf GdTGe,J (B624 (3g` s
(3ChdgG (B:s
(3bGd GdNWjH CHh HcQ CNHQfi GdYJjbi CfHCfG eMeO Hf GdYHGS s
(3BNQgG (B:s
(3heG PcQJg ef GdMcGjGJ hGdCSGfjO CNHQfi HgG hHLejY JGQjN GdNWjH TjNi CHh Gdjef RjO Hf GdMSf Hf RjO GdcfOi s
(3YdjgG ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B22s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B235 s
Keywords: (3GdJGQjNs